STRATEGI PEMANFAATAN RUANG TERBUKA HIJAU AKTIF UNTUK AKTIVITAS EKONOMI DI KECAMATAN SEMARANG SELATAN - Desinta Amelia Putri; Retno Sunu Astuti; R. Slamet Santoso (Journal of Public Policy and Management Review, 2023)
Existence of active green open space is accessible to society as public space that has impact on economy. Park becomes space where people interact with each other, but it hasn’t been used maximally for economy. This research aims to strategize increase of utilization of active green open space for economic activity in South Semarang Subdistrict. This research uses qualitative descriptive method that is based on primary and secondary data resources. Internal and external environment of organization result in the formulation of strategy issue that is analyzed by using quadrant charts of SWOT analysis. The result of research shows that internal strengths of organization that are congruence of vision, mission, and organizational purpose, adequacy of human resources, various supporting facilities, CSR program, and organization possibilities that are stability of society’s political condition, society’s support of street vendors, and regulation that supports supporting factor to increase economic activity of active green open space. Strategy issue is calculated by giving weight and rating, its position is in quadrant I as very advantageous position with aggressive strategy. Formulated strategies are increasing society’s productive economy, mapping active parks for society’s economic activity, setting special location for micro, small, and medium-sized enterprises that are around the park, and developing area of active park by adding complementary facilities and actively including society.